Formy adresatywne w społeczności internetowej kobiet. Na materiale wybranych komentarzy do podcastu Yeodultok - Łojko, Zuzanna (Humaniora. Czasopismo Internetowe, 2025)
The Korean Language has a complex system of terms of address (kor. hochingeo, 호칭어) that informs about the relationship between the interlocutors and prescribed roles interlocutors take on in a given community. Terms of address have been a subject of many studies, as their usage evolves amidst social changes. However, little has been explored about how the terms of address are being used by online communities. The main aim of this paper is to examine the use of the terms of address in women online community based on comments published to the episodes of Women Talk (kor. Yeoja Duri Tokeuhago Itseumnida, 여자 둘이 토크하고 있습니다) podcast, published over the period from December 2, 2024 and January 31, 2025. The article discusses the types, structure and functions of the terms of address, as well as the influence of anonymity factor on their selection. Study reveals that the forms of address typical for the vernacular language are used in the virtual reality alongside the terms, developed on the Internet. Their use is determined by the criterion of anonymity. Apart from denoting a listener, terms of address are used in order to indicate a level of intimacy between speakers and listeners, reinforce a sense of belonging and strengthen bonds among the community members.